Sorry I don’t know the answer and also sorry about that other comment they are very rude I hope you find someone who actually knows the answer!! ❤️
I don't know what method is referred to in "section 4.3", but I'll suppose it's reduction of order and use that to find the exact solution. Take
![z=y'](https://tex.z-dn.net/?f=z%3Dy%27)
, so that
![z'=y''](https://tex.z-dn.net/?f=z%27%3Dy%27%27)
and we're left with the ODE linear in
![z](https://tex.z-dn.net/?f=z)
:
![y''-y'=0\implies z'-z=0\implies z=C_1e^x\implies y=C_1e^x+C_2](https://tex.z-dn.net/?f=y%27%27-y%27%3D0%5Cimplies%20z%27-z%3D0%5Cimplies%20z%3DC_1e%5Ex%5Cimplies%20y%3DC_1e%5Ex%2BC_2)
Now suppose
![y](https://tex.z-dn.net/?f=y)
has a power series expansion
![y=\displaystyle\sum_{n\ge0}a_nx^n](https://tex.z-dn.net/?f=y%3D%5Cdisplaystyle%5Csum_%7Bn%5Cge0%7Da_nx%5En)
![\implies y'=\displaystyle\sum_{n\ge1}na_nx^{n-1}](https://tex.z-dn.net/?f=%5Cimplies%20y%27%3D%5Cdisplaystyle%5Csum_%7Bn%5Cge1%7Dna_nx%5E%7Bn-1%7D)
![\implies y''=\displaystyle\sum_{n\ge2}n(n-1)a_nx^{n-2}](https://tex.z-dn.net/?f=%5Cimplies%20y%27%27%3D%5Cdisplaystyle%5Csum_%7Bn%5Cge2%7Dn%28n-1%29a_nx%5E%7Bn-2%7D)
Then the ODE can be written as
![\displaystyle\sum_{n\ge2}n(n-1)a_nx^{n-2}-\sum_{n\ge1}na_nx^{n-1}=0](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Csum_%7Bn%5Cge2%7Dn%28n-1%29a_nx%5E%7Bn-2%7D-%5Csum_%7Bn%5Cge1%7Dna_nx%5E%7Bn-1%7D%3D0)
![\displaystyle\sum_{n\ge2}n(n-1)a_nx^{n-2}-\sum_{n\ge2}(n-1)a_{n-1}x^{n-2}=0](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Csum_%7Bn%5Cge2%7Dn%28n-1%29a_nx%5E%7Bn-2%7D-%5Csum_%7Bn%5Cge2%7D%28n-1%29a_%7Bn-1%7Dx%5E%7Bn-2%7D%3D0)
![\displaystyle\sum_{n\ge2}\bigg[n(n-1)a_n-(n-1)a_{n-1}\bigg]x^{n-2}=0](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Csum_%7Bn%5Cge2%7D%5Cbigg%5Bn%28n-1%29a_n-%28n-1%29a_%7Bn-1%7D%5Cbigg%5Dx%5E%7Bn-2%7D%3D0)
All the coefficients of the series vanish, and setting
![x=0](https://tex.z-dn.net/?f=x%3D0)
in the power series forms for
![y](https://tex.z-dn.net/?f=y)
and
![y'](https://tex.z-dn.net/?f=y%27)
tell us that
![y(0)=a_0](https://tex.z-dn.net/?f=y%280%29%3Da_0)
and
![y'(0)=a_1](https://tex.z-dn.net/?f=y%27%280%29%3Da_1)
, so we get the recurrence
![\begin{cases}a_0=a_0\\\\a_1=a_1\\\\a_n=\dfrac{a_{n-1}}n&\text{for }n\ge2\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7Da_0%3Da_0%5C%5C%5C%5Ca_1%3Da_1%5C%5C%5C%5Ca_n%3D%5Cdfrac%7Ba_%7Bn-1%7D%7Dn%26%5Ctext%7Bfor%20%7Dn%5Cge2%5Cend%7Bcases%7D)
We can solve explicitly for
![a_n](https://tex.z-dn.net/?f=a_n)
quite easily:
![a_n=\dfrac{a_{n-1}}n\implies a_{n-1}=\dfrac{a_{n-2}}{n-1}\implies a_n=\dfrac{a_{n-2}}{n(n-1)}](https://tex.z-dn.net/?f=a_n%3D%5Cdfrac%7Ba_%7Bn-1%7D%7Dn%5Cimplies%20a_%7Bn-1%7D%3D%5Cdfrac%7Ba_%7Bn-2%7D%7D%7Bn-1%7D%5Cimplies%20a_n%3D%5Cdfrac%7Ba_%7Bn-2%7D%7D%7Bn%28n-1%29%7D)
and so on. Continuing in this way we end up with
![a_n=\dfrac{a_1}{n!}](https://tex.z-dn.net/?f=a_n%3D%5Cdfrac%7Ba_1%7D%7Bn%21%7D)
so that the solution to the ODE is
![y(x)=\displaystyle\sum_{n\ge0}\dfrac{a_1}{n!}x^n=a_1+a_1x+\dfrac{a_1}2x^2+\cdots=a_1e^x](https://tex.z-dn.net/?f=y%28x%29%3D%5Cdisplaystyle%5Csum_%7Bn%5Cge0%7D%5Cdfrac%7Ba_1%7D%7Bn%21%7Dx%5En%3Da_1%2Ba_1x%2B%5Cdfrac%7Ba_1%7D2x%5E2%2B%5Ccdots%3Da_1e%5Ex)
We also require the solution to satisfy
![y(0)=a_0](https://tex.z-dn.net/?f=y%280%29%3Da_0)
, which we can do easily by adding and subtracting a constant as needed:
Answer:
Her answer should have been x=17/34
Step-by-step explanation: